Cytology cell blocks are suitable for immunohistochemical testing for PD-L1 in lung cancer. (12th April 2018) - Wang, H; Agulnik, J; Kasymjanova, G; Wang, A; Jiménez, P; Cohen, V; Small, D; Pepe, C; Sakr, L; Fiset, P O; Auger, M; Camilleri-Broet, S; et al.
Abstract: Background: PD-L1 immunohistochemistry (IHC) testing is usually carried out on tissue blocks from core needle biopsy or surgical resections. In this study, we assessed the feasibility of using cytology cell blocks for PD-L1 IHC assay. Methods: A total of 1419 consecutive cases of non-small-cell lung cancer (NSCLC), including 371 cytology cell blocks, 809 small biopsies, and 239 surgical specimens, were included in the study. The cytology cell blocks were prepared with formalin only, methanol/alcohol only or both. PD-L1 expression was examined by staining with Dako PD-L1 IHC 22C3 pharmDx kit. A Tumor Proportion Score (TPS) was categorized as <1%, 1%–49% and ≥50% tumor cells. A total of 100 viable tumor cells were required for adequacy. Results: Of the cytology cell blocks, 92% of the specimens had an adequate number of tumor cells, not significantly different from small biopsies. The rate of TPS ≥50% differed between sample types and was observed in 42% of cytology cell blocks versus 36% of small biopsies ( P = 0.04), and 29% of surgical resections ( P = 0.001). The fixative methods did not affect the immunostaining, with overall PD-L1 high expression (TPS ≥50%) rates of 42% in formalin-fixed specimens versus 40% in specimens with combined fixation by methanol/alcohol and formalin (NS). The PD-L1 high expression rate was not associated with EGFR, ALK or KRAS molecular alterations. Higher stage (IV) was associated with higher PD-L1 TPS ( P = 0.001). Conclusion: Our results show that when the TPS ≥50% is used as the end point, PD-L1 IHC performs well with cytology cell blocks. Cell blocks should be considered as a valuable resource for PD-L1 testing in advanced NSCLC. The clinical significance of higher PD-L1 IHC scores in cytology specimens needs to be evaluated prospectively.